Forbes best business mistakes : how today?s top business leaders turned missteps into success - Sellers, Bob , 1955- (John Wiley & Sons, 2010)
Based on the experiences of some of today's most successful men and women, this book contains practical lessons that can help you learn from their personal and professional missteps. The author sat down for exclusive and revealing interviews with each and every person profiled. He shares their stories to provide valuable insights into how to turn a bad business situation into a success.--[book cover]